EVALUATION OF THE EFFICACY OF A COMBINATION -MEASLES, MUMPS AND RUBELLA VACCINE IN THE TREATMENT OF PLANTAR WARTS - Nagat Sobhy Mohamad; Fayrouz Badran; Esraa Yakout (Our Dermatology Online, 2013)
Introduction: The treatment of patients with plantar warts continues to be a frustrating matter for both primary care physicians and dermatologists. There are new trends towards the use of immunotherapy in treatment of warts, as the immune system seems to play an important role in the control of warts infection. Aim: Assessing the efficacy of intralesional injection of MMR vaccine (measles, mumps, rubella) in the treatment of plantar warts. Patients: One hundred patients complaining of plantar warts were included in this study. Methods: The patients were divided into two groups: Group 1: This group included 50 patients subjected to intralesional injection of measles, mumps, rubella vaccine (MMR). Group 2: This group included 50 patients as a control group and subjected to intralesional injection of 0.3 ml saline. Only single wart was injected. Injections were done at 3-weeks interval until complete clearance or for a maximum of 3 treatments. Follow up of patients was done every month for six months for clinical assessment of results and to show any recurrence. Results: Regarding the response of the target wart, MMR- treated group showed significantly higher rate of complete clearance compared with the control group (82% versus 0% respectively). The rate of partial response was 6% versus 30%, and the rate of no response was 12% versus 70%, respectively. Regarding the response of untreated distant warts, MMR-treated group showed 86.9% complete and 13.1% partial clearance of the warts whereas the control group showed 100% no response. This strongly indicates the development of a widespread HPV-targeted immunity as a response of antigen injection and represents a major advantage of the intra lesional immunotherapy. Conclusions: We found that treatment of plantar warts by MMR vaccine is effective, with good cure rates and excellent safety profile..